Learning to breathe - White, Karen (Karen S.) (NAL Accent, 2007)
Brenna O'Brien doesn't believe in happy endings. Not since the love of her life, Pierce McGovern, left her years ago without a word. Now, she leads a quiet life surrounded by her four matchmaking sisters, running a historic movie theater and collecting old wartime letters. But she leaves the letters unopened, preferring to imagine their possibilities rather than risk being disappointed. Then Pierce comes back to town, shattering Brenna's hard-earned peace-and forcing her to re-examine everything, and realize that if she doesn't come to terms with the life she let slip away, she may never have the courage to go after the life she wants.